The Koran a very short introduction - Cook, Michael 1940- (Very short introductions, 2000)
Exploring the significance of the Koran in traditional Muslim culture, Michael Cook provides an account of the Koran as codex as scripture, as liturgy, and as the embodiment of truth, and examines its means of formation and dissemination